Studying International Students’ Cyclical Transformation - Fujuan Tan (Adult Education Research Conference, 2010)
Research on transformation has focused mostly on linear transformation in one direction. Little research has been conducted regarding transformation that can occur as a result of international students re-entering their home cultures, and the continuing potential for transformation as this cycle repeats itself. Further research should be developed to include more complex concepts of cyclical, as well as traditional linear transformation. This research acknowledges and discusses the need, benefits and possible directions of such research.